IMPROVING STUDENTS’ ENGLISH COMMUNICATION CAPABILITY THROUGH HABITUAL SPOKEN AND WRITTEN - SIHAR PARDEDE (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2023)
The objectives of this research are to find out whether the use of communication in habitual activities improves the students' speaking capability to do interaction in English spoken and written, the This research consisted of two cycles in which there were four steps in each cycle, namely planning, implementing, observation, and reflection. The researcher collected quantitative data of speaking and writing tests and qualitative data of classroom situation, field note, photograph, interview, and questionnaires. The results are (1) the students' speaking skill improved, the improvement of speaking score from 3. 86 up to 5.95 (2) Direct interview and written type established good communication activity between the teacher and the student and improved classroom management. On the other hand the disadvantage of direct interview and written type was difficulty in time management to conduct one to one interview with students in a big speaking and writing class. Therefore, the teacher should arrange good time allocation in large class to achieve the best outcome. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui apakah penggunaan komunikasi dalam kegiatan pembiasaan meningkatkan kemampuan berbicara siswa untuk melakukan interaksi dalam bahasa Inggris lisan dan tulisan, Penelitian ini terdiri dari dua siklus dimana terdapat empat langkah dalam setiap siklusnya, yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Peneliti mengumpulkan data kuantitatif tes berbicara dan menulis dan data kualitatif situasi kelas, catatan lapangan, foto, wawancara, dan angket. Hasilnya adalah (1) keterampilan berbicara siswa meningkat, peningkatan nilai berbicara dari 3,86 menjadi 5,95 (2) Wawancara langsung dan tulisan membentuk aktivitas komunikasi yang baik antara guru dan siswa serta pengelolaan kelas yang lebih baik. Di sisi lain kelemahan dari wawancara langsung dan tertulis adalah kesulitan dalam manajemen waktu untuk melakukan wawancara satu lawan satu dengan siswa di kelas berbicara dan menulis yang besar. Oleh karena itu, guru harus mengatur alokasi waktu yang baik di kelas besar untuk mencapai hasil yang terbaik.